Characterization of Carrageenan Edible films Plasticized with Glycerol - Arham Rusli; M. Metusalach; Mulyati Muhammad Tahir (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Concentration of base materials and plasticizers used in the formulation of edible film was believed to affect physical characteristics of the film. The objectives of this study were to evaluate the effects of base material (carrageenan) and plasticiser (glycerol) concentrations on the characteristics of edible films produced and to determine the best concentrations of these two components based on the physical characteristics of the films. The experiment was conducted using a completely randomized factorial design with triplicated. The treatments applied were the concentrations of carrageenan (1%, 2%, and 3% (w/v)) and glycerol (5%, 10%, and 15% (w/w)). The results showed that carrageenan and glycerol concentrations used in the formulation of edible film affect the edible film characteristics. Film thickness and moisture content were significantly influenced by carrageenan and glycerol concentrations, while film elongation was only affected by carrageenan concentration. The best physical characteristic of the edible films was obtained when carrageenan and glycerol concentrations were 3% and 10% respectively.